Behaviour of the kinematic parameters during a time to exhaustion test at VO2max in elite swimmers - Daniel Marinho (2006)
The aim of this study was to analyse, in swimming-pool conditions, the behaviour of the kinematic parameters - stroke rate (SR), stroke length (SL) and stroke index (SI) - during a time to exhaustion test performed at the minimum velocity that elicits maximal oxygen uptake (TLim-v O2max) in elite freestyle swimmers. Eleven swimmers from the National Portuguese Swimming Team (5 male and 6 female) performed an intermittent incremental test for v O2max assessment and an all-out swim at v O2max to determine TLim-v O2max and to analyse the evolution of the kinematic parameters throughout the test. SR increased and SL (and SI) decreased during the TLim-v O2max test, as a general tendency. When the differences in SR, SL and SI between each 12.5% section of the test were tested, a significant increase in SR and a decrease in SL and SI was verified at 25% [(74.00 (25.83 m)], 50% [(148.10 (51.66 m)] and 87.5% [(259.15 (90.41 m)] of the TLim-v O2max duration. These data showed a reduction of the propelling efficiency throughout such a test. These findings could be useful when designing training programmes, namely of middle distance swimmers, taking into consideration maximum aerobic speed, time to exhaustion and propelling efficiency.